From clinic to mechanism: Proteomics‐based assessment of angiogenesis in adrenal pheochromocytoma. Issue 12 (20th May 2019) - Sun, Fukang; Zhuo, Ran; Ma, Wenming; Yang, Da; Su, Tingwei; Ye, Lei; Xu, Danfeng; Wang, Weiqing
Abstract: Adrenal pheochromocytoma (PCC) is a very rare tumor that stems from chromaffin cells, which can develop into malignant tumor. During the operation, abundant blood vessels were often observed in PCC than other adrenal tumors, which increases the difficulty and risk of the surgery. Therefore, it is important to investigate the mechanism of PCC angiogenesis. Twelve surgical specimens of PCC from Ruijin Hospital, Shanghai Jiaotong University were grouped into high and low microvessel density (MVD) group. They were also divided into rich blood supply and nonenriched blood supply group, according to computed tomography (CT) manifestation. Comparative proteomic analysis based on liquid chromatography–tandem mass spectrometry (LC–MS/MS) and bioinformatics analysis revealed that 206 proteins differentially regulated in the high MVD group compared with low MVD group ( p  < 0.05). Besides, 61 proteins were discovered to be significantly changed when the 12 samples were grouped according to CT manifestation. By intersecting the differentially changed protein from MVD and CT grouping, 25 proteins were filtered out, with pathological function. COX4I2 was verified to be increased gradually with angiogenesis with increasing severity, and PLAT was shown to be decreased with angiogenesis in PCC, by quantitative reverse‐transcription polymerase chain reaction and immunohistochemistry. The quantitative proteomics result indicated that the tumor angiogenesis in PCC is associated with hypoxia. COX4I2 and PLAT were highly correlated with blood supply in PCC which contribute to angiogenesis in PCC, which could be used as biomarkers to better indicate tumor angiogenesis, or targets to regress tumor angiogenesis as treatment. Abstract : The quantitative proteomics was used to investigate the mechanism of pheochromocytoma (PCC) angiogenesis. COX4I2 was shown to be increased gradually with severer angiogenesis, and PLAT was shown to be decreased with angiogenesis, they might be used as biomarker to better indicate the tumor stage, or could be targeted to regress the angiogenesis.